Evaluation of Superior Cross Combinations and Identification of Better Parental Stocks from Early Clonal Trials in Sugarcane - Sreenivasa V.,; Amaresh,; , Aswini Nunavath; Dhanya V. G.,; Abhishek G. J.,; Mahadevaiah C.,; , Adhini S. Pazhany; , M. Alagupalamuthirsolai; , Arun Kumar; , A. Anna Durai; , Ravinder Kumar; , Meena Minturam; et al. (Archives of Current Research International, 2024)
Sugarcane is a clonally propagated crop and genetic improvement involves crossing of diverse species of Saccharum clones. Identification of desirable cross combination is one of the essential steps in the development of superior varieties. This study was conducted with an objective of identification of best cross combination based on their ability to produce superior clones by contributing desirable traits and suitability of a parental stock as “FEMALES” or “MALES” based on their ability to transmit positive genes to progeny. Sixteen biparental crosses with minimum of 20 progenies were screened for NMC (≥10) and HR Brix (≥20 units) in first clonal selection. The significance of parental stocks performance in cross combination was tested using “t‟ test assuming unequal variance. Progenies obtained from Co 06015, Co 0241 and Co 8347 recorded 20.99%, 20.82% and 20.81% of HR Brix, while Co 0209, Co 06015 and Co 94008 recorded 14.23, 12.76 and 11.88 of mean NMC when they used as male in crossing. Clones derived from Co 99006, Co 0403 and Co 06002 showed 20.93%, 20.82% and 20.81% of HR Brix, whereas Co 07010, Co 99006 and 2007-285 recorded 13.68, 12.21 and 11.40 mean NMC when they were used as female in crossing. Crosses viz., Co 99006 x Co 06015, Co 0403 x Co 0241, 2007-285 x Co 0209 and Co 94005 x Co 86011 has contributed 63%, 32%, 30% and 28% desirable selections respectively. The clones Co 06015 and Co 99006 are proven male and female can be used abundantly in crossing for the development of superior clones. The clones Co 8347, Co 0241, Co 0209 and Co 94008 are best males, whereas Co 0403, Co 06002, Co 07010 and 2007-285 are best females need to be crossed extensively for the development of superior varieties combining quality and cane yield traits.